1970
DOI: 10.1139/v70-427
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of some α-D-alkyl glucosides and mannosides: apparent molal volumes and solubilization of nitrobenzene in water at 25 °C

Abstract: Normal and cyclic a-D-alkyl glucosides and mannosides have been synthesized in a one-step procedure from the corresponding sugar. The apparent molal volume and the influence on the solubility of nitrobenzene of some of these glycosides have been measured in water at 25 "C. Evidence for micelle formation is presented for a-D-11-hexyl glucoside, -11-octyl glucoside, and -cyclohexyl mannoside. Comparison of the physical properties of the aqueous solutions shows that the stereochemistry of the sugar unit plays an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 4 publications
4
26
0
Order By: Relevance
“…Table 1. Values proposed in several published reports are within a similar range (17)(18)(19)(20)(21). The concentration of each AGs is about 3 times the critical micelle concentration.…”
Section: Introductionsupporting
confidence: 70%
“…Table 1. Values proposed in several published reports are within a similar range (17)(18)(19)(20)(21). The concentration of each AGs is about 3 times the critical micelle concentration.…”
Section: Introductionsupporting
confidence: 70%
“…Commercially available guests were used without further treatment. Pyranosides 50 [69] and 54 [70] were prepared according to published procedures. The host concentration was kept constant at 0.5 mm, and a soln.…”
Section: Experimental Partmentioning
confidence: 99%
“…Based on filling model studies and conformational analysis data (Brown et al 1970;Jarrell et al 1987), Mannock et al (1990) suggested that (i) the band at 1 715 cm-1 exhibited by the fl-anomer originated from hydrogen bonding between the 2-hydroxyl of the sugar moiety and the sn 2 C = O, and (ii) the configuration of the e-anomeric centre would not permit H-bond-256 ing interactions. These conclusions show the importance of intramolecular hydrogen bonding in the geometrical arrangement and the polymorphic phase behavior of bilayers composed of glycolipids.…”
Section: Intramolecular H-bonding In the Polar Head Of Dgdgmentioning
confidence: 99%